Examining the phenotypic heterogeneity of early autism spectrum disorder: subtypes and short‐term outcomes. (12th August 2015) - Kim, So Hyun; Macari, Suzanne; Koller, Judah; Chawarska, Katarzyna
Abstract : Background: Phenotypic heterogeneity among toddlers presenting with ASD symptoms complicates diagnostic considerations and limits our ability to predict long‐term outcomes. To address this concern, we sought to identify more homogeneous subgroups within ASD based on toddlers' clinical profiles in the second year of life, evaluating diagnostic stability and clinical outcomes within the subgroups 1–2 years later. Methods: One hundred toddlers referred for suspected ASD underwent comprehensive assessments at 22 months ( SD = 3) and 37 months ( SD = 4). At 22 months, they were clustered based on symptom severity, developmental skills, and adaptive functioning. Diagnostic stability and clinical outcomes were evaluated within the clusters. Results: Four clusters characterized by distinct clinical profiles at the time of the first diagnosis were identified. Diagnostic stability was excellent in 3 out of 4 clusters (93%–100%) and was lowest in the initially least affected cluster (85%). Autism symptom severity was stable, except for one group where it increased over time (16% of the sample). A large proportion of toddlers showed significant improvements in verbal and communication skills. Only a small group (17%) exhibited very low levels of functioning and limited gains over time. Conclusions: Diagnostic stability and developmental progression from the second to third year of life in toddlers with ASD vary depending on their initial early profiles of relative strengths and deficits. Although a small minority of toddlers with more complex clinical presentations may not retain their diagnoses by the age of three, most children continue to exhibit symptoms of autism. Despite limited improvements in symptom severity, many children show significant gains in verbal functioning. Only a small proportion of children (17%) exhibit very limited gains despite intensive intervention. These findings support continued efforts to examine determinants of developmental trajectories including factors mediating and moderating response to treatment.